Membangun Jembatan Antar Generasi: Strategi Gereja Merangkul Milenial dan Generasi Z - Ibrahim, Ibrahim (EULOGIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract: This article discusses the church's theological and pastoral strategies in responding to the generational gap between seniors and Millennials and Generation Z in the digital age. This study uses a reflective qualitative approach with a contextual theological framework through a literature study of contemporary theological and social literature. The results of the study show that the crisis in the involvement of the younger generation is not only due to technological changes, but also the incompatibility of the church's spiritual paradigm with the faith needs of the digital generation. Millennials and Gen Z want a community that is authentic, open, and relevant to the realities of life. Therefore, the church needs to reinterpret its calling incarnation, presenting God's love in digital culture and cross-generational relationships. The proposed strategies include the formation of communities as safe spaces, collaborative leadership, and digital-based faith building. Thus, the multigenerational church becomes a form of trinitarian ecclesiology that integrates differences as the richness of God's love for the modern world.  Keywords: Church; Millennials; Generation Z; Contextual Theology; Digital; Multigenerational. Abstrak: Artikel ini membahas strategi teologis dan pastoral gereja dalam merespons kesenjangan generasi antara kaum senior dengan generasi Milenial dan Generasi Z di era digital. Penelitian ini menggunakan pendekatan kualitatif reflektif dengan kerangka teologi kontekstual melalui studi pustaka terhadap literatur teologi dan sosial kontemporer. Hasil kajian menunjukkan bahwa krisis keterlibatan generasi muda bukan sekadar akibat perubahan teknologi, tetapi juga ketidaksesuaian paradigma spiritual gereja dengan kebutuhan iman generasi digital. Milenial dan Gen Z menghendaki komunitas yang otentik, terbuka, dan relevan dengan realitas hidup. Karena itu, gereja perlu menafsir ulang panggilannya secara inkarnasional, menghadirkan kasih Allah dalam budaya digital dan relasi lintas generasi. Strategi yang diusulkan mencakup pembentukan komunitas sebagai ruang aman, kepemimpinan kolaboratif, dan pembinaan iman berbasis digital. Dengan demikian, gereja multigenerasi menjadi wujud eklesiologi trinitaris yang mengintegrasikan perbedaan sebagai kekayaan kasih Allah bagi dunia modern. Kata kunci: Gereja; Milenial; Generasi Z; Teologi Kontekstual; Digital; Multigenerasi